Experimental and numerical study of heat transfer in hot machined workpiece using infrared radiation - Sanchez, Luiz Eduardo de Ângelo [UNESP]; Scalon, Vicente Luiz [UNESP]; Módolo, Délson Luiz [UNESP] (My University, 2014)
One of the greatest problems found in machining is related to the cutting tool wear. A way for increasing the tool life points out to the development of materials more resistant to wear, such as PCBN inserts. However, the unit cost of these tools is considerable high, around 10 to 20 times compared to coated carbide insert, besides its better performance occurs in high speeds requiring modern machine tools. Another way, less studied is the workpiece heating in order to diminish the shear stress material and thus reduce the machining forces allowing an increase of tool life. For understanding the heat transfer influences by conduction in this machining process, a mathematical model was developed to allow a simplified numerical simulation, using the finite element method, in order to determine the temperature profiles inside the workpiece.
Keywords: Hot machining; Turning; Tool life; Heat transfer; Finite element method